UTILIZATION OF CROP RESIDUES FOR LIVESTOCK FEEDS AMONG RURAL DWELLERS IN OSUN STATE, NIGERIA - Musa, M. O.; Bolarin, O.; Ajayi, F. O.; Ojo, O. O. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
This study examined the utilization of crop residues for livestock feeds among rural dwellers in Osun State, Nigeria. A multi-stage sampling technique was used in selecting 200 respondents. Data were collected using interview schedule and analyzed using descriptive statistics and multiple regression. The results revealed that the average age of the respondents was 58.1 years. Also, the crop residue mostly used by respondents was cassava peel (98.5%) and yam peels (96.0%). All (100.0%) of the respondents had knowledge that crop residues could be used for livestock feeds, while majority (64.0%) of the respondents were grouped as having low utilization. Barriers that hindered utilization of crop residues for livestock feeds were difficulty in processing crop residues (x̄ =1.86) and inability to collect and transport (x̄ =1.77). The results of the regression analysis revealed that gender (β= -2.73), household size (β=0.73), level of education (β=1.79) and income (β=5.00) were significant in influencing the utilization of crop residues for livestock feeds among respondents in the study area. The study concluded that utilization of crop residues for livestock feeds was influenced by gender, household size, level of education, income of the rural dwellers in the study area. The study recommends the need for extension organizations to organize workshops on crop residue management, focusing on nutritional value, processing and storage techniques among rural dwellers raising livestock in the study area.